Thermodynamic Study on Hydrotropic Aggregation Behavior of Theophylline - Jayakumar, Chinnakannu; Reddy Prasad, D.M (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: A systematic study is required to enhance the solubility of insoluble fluid drugs that are only sparingly soluble. Hydrotropy may be a distinctive development to reinforce the liquid solubility of poorly water-soluble drugs. Materials and Methods: The term hydrotropic has been wont to designate the rise in the solubility of assorted substances in water because of the presence of enormous amounts of additives. Sodium salicylate, sodium benzoate, and resorcinol are utilized to reinforce the liquid solubility of many poorly soluble drugs. Varied organic solvents like methyl alcohol, chloroform, alcohol, dimethylformamide, and benzene are utilized for the solubilization of poorly soluble drugs. Theophylline drug was accessories to numerous hydrotrope concentrations (0-3 mol/L) and also the non-inheritable sample for a solubility determination was analyzed in an exploitation UV spectrophotometer. Results: The solubility of theophylline has been specifically found to improve with an increase in hydrotrope concentration and also with a device temperature likely to be close to that of other organic compounds and drugs. Conclusion: To initiate substantial solubilization of the theophylline compound, a minimum hydrotrope concentration (MHC) in the aqueous phase was needed. As a consequence of the improvement in the solubilization of theophylline, the coefficient of mass transfer was also observed to expand with an increase in the hydrotropic concentration at 303 K. To have a substantial enhancement within the mass transfer coefficient, a threshold value equivalent to MHC is to be maintained. For all sets of experiments, the maximal enhancement factor, which is the value ratio between the presence and absence of a hydrotrope, has been calculated. Thermodynamic parameters such as Gibb’s free energy, enthalpy, and entropy of theophylline were calculated to determine the hydrotropic aggregation activity of theophylline. With an increase in system temperature, Gibb’s free energy declines. It was found that the aggregation of hydrotropes was exothermic and preferred by a positive entropy value.
Keywords: Hydrotropy; Theophylline; Solubility; Enhancement Factor; Aggregation Properties